Yoga Books : Yoga for Children Step by Step - YAMINI MUTHANNA (India Om, 2022)
All children need an outlet to handle the pressures they face.The modern-day education system and lifestyle place them under a lot of stress.The degree of stress varies from child to child, depending on their age and the environment they are in. Practising yoga is the perfect way to bring harmony to the mind and help children build healthier and happier lives. Yoga for Children features several yoga poses along with step-by-step guidance and detailed instructions for adults to help and guide children. The sequences in this book are categorised specifically to address issues children face in their growing years. Yamini Muthanna, an experienced yoga practitioner and teacher, has put these together based on her observations while interacting with children over the years. Parents and teachers can initiate children into the practice of yoga using this excellent and easy-to-follow guide. Let children choose a routine that appeals to them.
Keywords: Everything Sports -- Everything Sports; Recreational Activities -- Recreational Activities